2022
DOI: 10.1186/s12889-022-12638-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the uptake, retention and effectiveness of exercise referral schemes for the management of mental health conditions in primary care: a systematic review

Abstract: Background Exercise is a recognised element of health-care management of mental-health conditions. In primary health care, it has been delivered through exercise referral schemes (ERS). The National Institute for Health and Care Excellence has highlighted uncertainty regarding the effectiveness of ERS in improving exercise participation and health outcomes among those referred for mental-health reasons. This review aims, therefore, to evaluate ERSs for individuals who are referred specifically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Community physical activity referral schemes should also be considered. A 2022 review of exercise referral schemes for mental health found that schemes that involved face-to-face consultations and telephone calls had the highest rates of mean uptake [44], for example referrals to local leisure centres. Referrals should be tailored to individual patient preferences and consider the unique individual and contextual barriers.…”
Section: How To Assess and Promote Physical Activity In Clinical Prac...mentioning
confidence: 99%
“…Community physical activity referral schemes should also be considered. A 2022 review of exercise referral schemes for mental health found that schemes that involved face-to-face consultations and telephone calls had the highest rates of mean uptake [44], for example referrals to local leisure centres. Referrals should be tailored to individual patient preferences and consider the unique individual and contextual barriers.…”
Section: How To Assess and Promote Physical Activity In Clinical Prac...mentioning
confidence: 99%
“…Exercise-referral schemes using regular phone calls and face-to-face consultations with social support (e.g., by a family member) have been shown to be efective for clients' long-term physical activity levels [53]. In the United Kingdom, 80% of clients from general practitioners experiencing depression are referred to as using such exercise-referral schemes [54].…”
Section: Discussionmentioning
confidence: 99%
“…For example, raised levels of predictive biomarkers, like HbA1c, may highlight patients who would benefit from additional interventions suited to their needs [ 14 ]. Tailoring programmes to the individual has been shown to support long-term adherence [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%